(untitled) (New York, 2011)
This unique text provides a broad introduction to qualitative analysis together with concrete demonstrations and comparisons of five major approaches. Leading scholars apply their respective analytic lenses to a narrative account and interview featuring "Teresa," a young opera singer who experienced a career-changing illness. The resulting analyses vividly exemplify what each approach looks like in action. The researchers then probe the similarities and differences among their approaches; their distinctive purposes and strengths; the role, style, and subjectivity of the individual researcher; and the scientific and ethical complexities of conducting qualitative research. Also included are the research participant's responses to each analysis of her experience. A narrative account from another research participant, "Gail," can be used by readers to practice the kinds of analysis explored in the book.
Keywords: Nghiên cứu định tính,Nghiên cứu định tính,Psychology,Qualitative research; Tâm lý học,Qualitative research